Pretransplant Immediately Early‐1‐Specific T Cell Responses Provide Protection for CMV Infection After Kidney Transplantation. Issue 7 (24th May 2013) - Bestard, O.; Lucia, M.; Crespo, E.; Van Liempt, B.; Palacio, D.; Melilli, E.; Torras, J.; Llaudó, I.; Cerezo, G.; Taco, O.; Gil‐Vernet, S.; Grinyó, J. M.; et al.
Abstract Cytomegalovirus (CMV) infection is still a major complication after kidney transplantation. Although cytotoxic CMV‐specific T cells play a crucial role controlling CMV survival and replication, current pretransplant risk assessment for CMV infection is only based on donor/recipient (IgG)‐serostatus. Here, we evaluated the usefulness of monitoring pre‐ and 6‐month CMV‐specific T cell responses against two dominant CMV antigens (IE‐1 and pp65) and a CMV lysate, using an IFN‐γ Elispot, for predicting the advent of CMV infection in two cohorts of 137 kidney transplant recipients either receiving routine prophylaxis (n = 39) or preemptive treatment (n = 98). Incidence of CMV antigenemia/disease within the prophylaxis and preemptive group was 28%/20% and 22%/12%, respectively. Patients developing CMV infection showed significantly lower anti‐IE‐1‐specific T cell responses than those that did not in both groups (p < 0.05). In a ROC curve analysis, low pretransplant anti‐IE‐1‐specific T cell responses predicted the risk of both primary and late‐onset CMV infection with high sensitivity and specificity (AUC > 0.70). Furthermore, when using most sensitive and specific Elispot cut‐off values, a higher than 80% and 90% sensitivity and negative predictive value was obtained, respectively. Monitoring IE‐1‐specific T cell responses before transplantation may be useful for predicting posttransplant risk of CMV infection, thus potentially guiding decision‐making regarding CMV preventive treatment.